Macroeconomic impact of transport investment in Romania during the socialist period (1950–1989) - Teclean, Cezar (Studia Historiae Oeconomicae, 2025)
In this study we investigate the relationships between the investments allocated to transport systems and the economic development of Romania in the socialist era (1950–1989). The objective of our analysis aims at the quantitative evaluation of the correlation between the two mentioned components, in order to quantify the developmental potential of investments in transport during the analyzed period. For this purpose, we consider as variables transport investment, fixed capital in transport and the contribution of transport investment to the design of national income, for which we use the data available in the official statistical bases. For the proposed evaluation, we quantified the impact of transport investment on the gross national income (GNI ) using the econometric model of correlation and determination coefficients. At the same time, we have measured the lucrativeness of transport investment by referring to the contribution of transport to GNI . The comparative chronological evaluation of the obtained results suggests a differential impact over time of transport investment on GNI , as well as a differential evolution of the economic lucrativeness of these investments. Our findings show that the return on transport investments had a linear upward evolution especially after 1970, while the developmental impact of these investments described a symmetric-historical trajectory with the most robust effect on national income in the middle of the communist period (1961–1980), but with little impact at the beginning and end of the socialist era. Quantitative radiography of the impact of transport investment on GNI in the socialist era paints a less-discussed facet of recent economic history useful for understanding the roadmap of statist economies in Central and Eastern Europe.